Managing and visualising geochemical data for tephra correlation with the IntChron Integration Tool - Victoria C. Smith; Danielle McLean; Eloise Wilkinson‐Rowe; Emma L. Horn; Gavin Kane; Christopher Bronk Ramsey (Journal of Quaternary Science, 2026)
There is now a wealth of glass‐shard geochemical data for volcanic ash (tephra) layers from a wide range of volcanoes and eruptions, providing invaluable datasets for tephrochronology. However, compilation of published data to assess tephra correlations leads to large files and requires careful management. Here, we show that a project within the IntChron Integration Tool (Ramsey et al., 2019), an open‐access and versatile online application, can be used to effectively store and manage tephra information, geochemical data and relevant metadata, while also providing visualisation and statistical tools. The visualisation functionality allows sites to be plotted on a variety of base maps, enables the plotting of tephra shard concentrations through a sequence and generates biplots of major and trace elements. The statistical tools are similarly invaluable for investigating compositional variability and relationships, and for assessing the probability that datasets correlate. An IntChron Integration Tool project supports the entire workflow, from sample and data collection through analysis and interpretation, to the generation of publication‐ready plots. Here, we present an example project to show the functionality using published data from distal tephra layers in the Lake Suigetsu core, and proximal eruption deposits from volcanoes across Japan. This project contains over 7000 geochemical analyses from 12 publications, demonstrating the power of the IntChron Integration Tool to manage, visualise and archive geochemical datasets.

Effects of secondary hydrothermal fluids on gallium distribution and coordination in hot springs silica using Ga K-edge XANES - M.C. Rowe; K.A. Campbell; D.A. Stallard; B. Lyon; A. Langendam; E. Kalinina; M. Yamanaka; R. Tanaka; T. Christopher; S.W. Ruff; E. Nersezova; T. Ota; et al. (Applied Geochemistry, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Faunal community ecology of central-eastern Indian Ocean Seamounts - Timothy D. O'Hara; Shane T. Ahyong; Phil Alderslade; Dianne Bray; Francesco Criscione; Niki Davey; Caroline Farrelly; Martin F. Gomon; Ana Hara; Jeremy Horowitz; Andrew M. Hosie; Lisa Kirkendale; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Estimating mercury exposure in amphibians using non-lethal tissue sampling - Caitlin T. Rumrill; Kelly L. Smalling; Colleen Emery; Blake R. Hossack; Brian J. Halstead; Michael J. Adams; Adam R. Backlin; Adrianne B. Brand; Jon M. Davenport; Robert N. Fisher; Jill Fleming; Brad M. Glorioso; et al. (Ecotoxicology, 2026)

Genomics Reveals Extensive Population Structure and Undescribed Phylogenetic Relationships in the Cascade Torrent Salamander ( Rhyacotriton cascadae ) - Christopher D. Cousins; Deanna H. Olson; Lindsay S. Millward; Michael J. Adams; Christopher A. Pearl; Jennifer C. Rowe; Tiffany S. Garcia (Journal of Biogeography, 2026)
Aim Aims of the study are to examine patterns of range‐wide genetic differentiation and population structure in a headwater obligate salamander living in a geologically rich region, to identify genetically distinct populations and areas of gene flow between them. Location Oregon and Washington in the Pacific Northwest, United States of America. Time Period Tissue samples were collected in 2022 and 2023. Major Taxa Studied The Cascade torrent salamander Rhyacotriton cascadae . Methods Utilisation of a genome‐wide single nucleotide polymorphism (SNP) dataset from across the species range to conduct a principal components analysis (PCA), Bayesian model of population structure, co‐ancestry matrix, phylogenetic tree and estimate genetic diversity. Results There are extensive levels of population structure within R. cascadae , including a previously unknown and highly differentiated clade. Structure is characterised by an island‐like pattern wherein the species is comprised of six populations that function as independent demographic units, with gene flow largely constrained within populations. Main Conclusions Our findings reveal cryptic population structure within R. cascadae , identifying six distinct populations across the range. The northernmost population in the northwest of the species range in Washington is surprisingly highly divergent from the other five populations, and the divergence was not previously known to science. While major rivers act as phylogeographic boundaries between some populations, these boundaries appear to not always be complete.

Decrypting the messages in the matrix: The proceedings of a symposium on dairy food matrix science and public health opportunities - Kevin B. Comerford; Allison L. Unger; Christopher J. Cifelli; Emma Feeney; Sylvia Rowe; Connie Weaver; Katie Brown (Critical Reviews in Food Science and Nutrition, 2025)

A 150,000-year lacustrine record of the Indo-Australian monsoon from northern Australia - Michael I. Bird; Michael Brand; Rainy Comley; Xennephone Hadeen; Zenobia Jacobs; Cassandra Rowe; Frédérik Saltré; Christopher M. Wurster; Costijn Zwart; Corey J.A. Bradshaw (Quaternary Science Reviews, 2025)

Holocene hydroclimate inferred from alkane isotope and pollen records from monsoonal northern Australia - Michael I. Bird; Michael Brand; Rainy Comley; Xennephone Hadeen; Niels C. Munksgaard; Cassandra Rowe; Christopher M. Wurster; Costijn Zwart (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Thermal Influences on Metabolic Rates in Hatchling Northern Diamondback Terrapins (Malaclemys terrapin terrapin) from the Chesapeake Bay - Christopher L. Rowe; Sarah A. Funck (Estuaries and Coasts, 2025)

Comparing pollen and n-alkane carbon isotope records in a tropical lacustrine environment - Xennephone Hadeen; Cassandra Rowe; Michael Brand; Rainy Comley; Sourav Das; Christopher M. Wurster; Costijn Zwart; Michael I. Bird (Quaternary Science Reviews, 2025)

Brainstem Substructure Atrophy in Late-Onset GM2-Gangliosidosis Imaging Using Automated Segmentation - Olivia E. Rowe; D. Rangaprakash; Florian S. Eichler; Jeremy D. Schmahmann; Robert L. Barry; Christopher D. Stephen (The Cerebellum, 2025)

Thermal-metabolic relationships in hatchling snapping turtles during simulated seasonal cooling - Christopher L. Rowe (Acta Oecologica, 2024)

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Vegetation changes through stadial and interstadial stages of MIS 4 and MIS 3 based on a palynological analysis of the Girraween Lagoon sediments of Darwin, Australia - Cassandra Rowe; Michael Brand; Christopher M. Wurster; Michael I. Bird (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Petrosal morphology of the Early Cretaceous triconodontid Astroconodon from the Cloverly Formation (Montana, USA) - Simone Hoffmann; E. Christopher Kirk; Timothy B. Rowe; Richard L. Cifelli (Journal of Mammalian Evolution, 2023)

Integrating risk assessment methods for carbon storage: A case study for the quest carbon capture and storage facility - Christopher F. Brown; Greg Lackey; Nate Mitchell; Seunghwan Baek; Brandon Schwartz; Marcella Dean; Robert Dilmore; Hein Blanke; Simon O'Brien; Carrie Rowe (International Journal of Greenhouse Gas Control, 2023)

Adjacent and downstream effects of forest harvest on the distribution and abundance of larval headwater stream amphibians in the Oregon Coast Range - Adam Duarte; Nathan D. Chelgren; Jennifer C. Rowe; Christopher A. Pearl; Sherri L. Johnson; Michael J. Adams (Forest Ecology and Management, 2023)

Sustainability of bioenergy – Mapping the risks & benefits to inform future bioenergy systems - Andrew James Welfle; Alberto Almena; Muhammad Naveed Arshad; Scott William Banks; Isabela Butnar; Katie Jane Chong; SamuelJ.G. Cooper; Helen Daly; Samira Garcia Freites; Fatih Güleç; Christopher Hardacre; Robert Holland; et al. (Biomass and Bioenergy, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Trends of extreme air temperature and precipitation and their impact on corn and soybean yields in Nebraska, USA - Carlos A. C. dos Santos; Christopher M. U. Neale; Mesfin M. Mekonnen; Ivo Zution Gonçalves; Gabriel de Oliveira; Osias Ruiz-Alvarez; Babak Safa; Clinton M. Rowe (Theoretical and Applied Climatology, 2022)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Monitoring wetland water quality related to livestock grazing in amphibian habitats - Kelly L. Smalling; Jennifer C. Rowe; Christopher A. Pearl; Luke R. Iwanowicz; Carrie E. Givens; Chauncey W. Anderson; Brome McCreary; Michael J. Adams (Environmental Monitoring and Assessment, 2021)
Land use alteration such as livestock grazing can affect water quality in habitats of at-risk wildlife species. Data from managed wetlands are needed to understand levels of exposure for aquatic life stages and monitor grazing-related changes afield. We quantified spatial and temporal variation in water quality in wetlands occupied by threatened Oregon spotted frog ( Rana pretiosa ) at Klamath Marsh National Wildlife Refuge in Oregon, United States (US). We used analyses for censored data to evaluate the importance of habitat type and grazing history in predicting concentrations of nutrients, turbidity, fecal indicator bacteria (FIB; total coliforms, Escherichia coli ( E. coli ), and enterococci), and estrogenicity, an indicator of estrogenic activity. Nutrients (orthophosphate and ammonia) and enterococci varied over time and space, while E. coli , total coliforms, turbidity, and estrogenicity were more strongly associated with local livestock grazing metrics. Turbidity was correlated with several grazing-related constituents and may be particularly useful for monitoring water quality in landscapes with livestock use. Concentrations of orthophosphate and estrogenicity were elevated at several sites relative to published health benchmarks, and their potential effects on Rana pretiosa warrant further investigation. Our data provided an initial assessment of potential exposure of amphibians to grazing-related constituents in western US wetlands. Increased monitoring of surface water quality and amphibian population status in combination with controlled laboratory toxicity studies could help inform future research and targeted management strategies for wetlands with both grazing and amphibians of conservation concern.

Carbon:nitrogen ratio as a proxy for tissue nonpolar lipid content and condition in black sea bass Centropristis striata along the Middle Atlantic Bight - Ginni A. La Rosa; Ryan J. Woodland; Christopher L. Rowe (Marine Biology, 2020)

mGluR5 Allosteric Modulation Promotes Neurorecovery in a 6-OHDA-Toxicant Model of Parkinson’s Disease - Kyle Farmer; Khaled S. Abd-Elrahman; Alexa Derksen; Elyn M. Rowe; Ashley M. Thompson; Christopher A. Rudyk; Natalie A. Prowse; Zachary Dwyer; Samantha C. Bureau; Teresa Fortin; Stephen S.G. Ferguson; Shawn Hayley (Molecular Neurobiology, 2020)

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

Effect of cattle exclosures on Columbia Spotted Frog abundance - Michael J. Adams; Christopher A. Pearl; Thierry Chambert; Brome McCreary; Stephanie K. Galvan; Jennifer Rowe (Wetlands Ecology and Management, 2018)

Self-reported confusion is related to global and regional β-amyloid: data from the Women’s healthy ageing project - Georgia E. McCluskey; Paul Yates; Victor L. Villemagne; Christopher Rowe; Cassandra E. I. Szoeke (Brain Imaging and Behavior, 2018)

Changes in Habitat Availability for Multiple Life Stages of Diamondback Terrapins (Malaclemys terrapin) in Chesapeake Bay in Response to Sea Level Rise - Ryan J. Woodland; Christopher L. Rowe; Paula F. P. Henry (Estuaries and Coasts, 2017)

Dietary Accumulation of Inorganic Selenium by a Larval Amphibian (Hyla chrysoscelis) and Influence on Accumulation of Background Mercury - Christopher L. Rowe; Andrew Heyes (Bulletin of Environmental Contamination and Toxicology, 2017)

3D Cosmic Ray Muon Tomography from an Underground Tunnel - Elena Guardincerri; Charlotte Rowe; Emily Schultz-Fellenz; Mousumi Roy; Nicolas George; Christopher Morris; Jeffrey Bacon; Matthew Durham; Deborah Morley; Kenie Plaud-Ramos; Daniel Poulson; Diane Baker; et al. (Pure and Applied Geophysics, 2017)

Performance on the Cogstate Brief Battery Is Related to Amyloid Levels and Hippocampal Volume in Very Mild Dementia - Yen Ying Lim; Victor L. Villemagne; Simon M. Laws; Robert H. Pietrzak; David Ames; Christopher Fowler; Stephanie Rainey-Smith; Peter J. Snyder; Pierrick Bourgeat; Ralph N. Martins; Olivier Salvado; Christopher C. Rowe; et al. (Journal of Molecular Neuroscience, 2016)

A Conceptualization of the Utility of Subjective Cognitive Decline in Clinical Trials of Preclinical Alzheimer’s Disease - Rachel F. Buckley; Victor L. Villemagne; Colin L. Masters; Kathryn A. Ellis; Christopher C. Rowe; Keith Johnson; Reisa Sperling; Rebecca Amariglio (Journal of Molecular Neuroscience, 2016)

Cities are hotspots for threatened species - Christopher D. Ives; Pia E. Lentini; Caragh G. Threlfall; Karen Ikin; Danielle F. Shanahan; Georgia E. Garrard; Sarah A. Bekessy; Richard A. Fuller; Laura Mumaw; Laura Rayner; Ross Rowe; Leonie E. Valentine; et al. (Global Ecology and Biogeography, 2016)
Aim Although urbanization impacts many species, there is little information on the patterns of occurrences of threatened species in urban relative to non‐urban areas. By assessing the extent of the distribution of threatened species across all A ustralian cities, we aim to investigate the currently under‐utilized opportunity that cities present for national biodiversity conservation. Location A ustralian mainland, T asmania and offshore islands. Methods Distributions of A ustralia's 1643 legally protected terrestrial species (hereafter ‘threatened species’) were compiled. We assessed the extent to which they overlapped with 99 cities (of more than 10,000 people), with all non‐urban areas, and with simulated ‘dummy’ cities which covered the same area and bioregion as the true cities but were non‐urban. We analysed differences between animals and plants, and examined variability within these groups using species accumulation modelling. Threatened species richness of true versus dummy cities was analysed using generalized linear mixed‐effects models. Results A ustralian cities support substantially more nationally threatened animal and plant species than all other non‐urban areas on a unit‐area basis. Thirty per cent of threatened species were found to occur in cities. Distribution patterns differed between plants and animals: individual threatened plant species were generally found in fewer cities than threatened animal species, yet plants were more likely to have a greater proportion of their distribution in urban areas than animals. Individual cities tended to contain unique suites of threatened species, especially threatened plants. The analysis of true versus dummy cities demonstrated that, even after accounting for factors such as net primary productivity and distance to the coast, cities still consistently supported a greater number of threatened species. Main conclusions This research highlights that A ustralian cities are important for the conservation of threatened species, and that the species assemblages of individual cities are relatively distinct. National conservation policy should recognize that cities play an integral role when planning for and managing threatened species.

The response of faunal biodiversity to an unmarked road in the Western Amazon - Andrew Whitworth; Christopher Beirne; Jasmine Rowe; Fraser Ross; Caroline Acton; Oliver Burdekin; Philip Brown (Biodiversity and Conservation, 2015)

Differential Patterns of Accumulation and Retention of Dietary Trace Elements Associated With Coal Ash During Larval Development and Metamorphosis of an Amphibian - Andrew Heyes; Christopher L. Rowe; Phillip Conrad (Archives of Environmental Contamination and Toxicology, 2014)

Dietary Selenomethionine Exposure Induces Physical Malformations and Decreases Growth and Survival to Metamorphosis in an Amphibian (Hyla chrysoscelis) - Laura Lockard; Christopher L. Rowe; Andrew Heyes (Archives of Environmental Contamination and Toxicology, 2013)

CCL20 Is Associated with Neurodegeneration Following Experimental Traumatic Brain Injury and Promotes Cellular Toxicity In Vitro - Christopher C. Leonardo; James Musso; Mahasweta Das; Derrick D. Rowe; Lisa A. Collier; Shyam Mohapatra; Keith R. Pennypacker (Translational Stroke Research, 2012)

The spleen contributes to stroke induced neurodegeneration through interferon gamma signaling - Hilary A. Seifert; Christopher C. Leonardo; Aaron A. Hall; Derrick D. Rowe; Lisa A. Collier; Stanley A. Benkovic; Alison E. Willing; Keith R. Pennypacker (Metabolic Brain Disease, 2012)

A Lagrangian Model to Predict the Modification of Near-Surface Scalar Mixing Ratios and Air–Water Exchange Fluxes in Offshore Flow - Mark D. Rowe; Judith A. Perlinger; Christopher W. Fairall (Boundary-Layer Meteorology, 2011)

Differential Patterns of Accumulation and Depuration of Dietary Selenium and Vanadium During Metamorphosis in the Gray Treefrog (Hyla versicolor) - Christopher L. Rowe; Andrew Heyes; Jessica Hilton (Archives of Environmental Contamination and Toxicology, 2011)

Amyloid Imaging in Alzheimer’s Disease and Other Dementias - Michelle T. Fodero-Tavoletti; Roberto Cappai; Catriona A. McLean; Kerryn E. Pike; Paul A. Adlard; Tiffany Cowie; Andrea R. Connor; Colin L. Masters; Christopher C. Rowe; Victor L. Villemagne (Brain Imaging and Behavior, 2009)

The ART of Loss: Aβ Imaging in the Evaluation of Alzheimer’s Disease and other Dementias - Victor L. Villemagne; Michelle T. Fodero-Tavoletti; Kerryn E. Pike; Roberto Cappai; Colin L. Masters; Christopher C. Rowe (Molecular Neurobiology, 2008)

Ecotoxicological Implications of Aquatic Disposal of Coal Combustion Residues In the United States: A Review - Christopher L. Rowe; William A. Hopkins; Justin D. Congdon (Environmental Monitoring and Assessment, 2002)